Environmental Fitness and Resilience A Review of Relevant Constructs, Measures, and Links to Well-Being - Shih, Regina A. (RAND Corporation, 2015)
This report is one of a series designed to support Air Force leaders in promoting resilience among its Airmen, civilian employees, and Air Force families. It identifies key environmental stressors experienced by Airmen and examines key resilience factors in the domain of environmental fitness, focusing specifically on prevention and protective measures.